Analysis Chip Devices: A Microfluidic Device with Continuous Ligand Gradients in Supported Lipid Bilayers to Probe Effects of Ligand Surface Density and Solution Shear Stress on Pathogen Adhesion (Adv. Mater. Interfaces 9/2016). Issue 9 (May 2016) - van Weerd, Jasper; Sankaran, Shrikrishnan; Roling, Oliver; Sukas, Sertan; Krabbenborg, Sven; Huskens, Jurriaan; le Gac, Séverine; Ravoo, Bart Jan; Karperien, Marcel; Jonkheijm, Pascal
Abstract : In article 1600055, Pascal Jonkheijm and co‐workers devise a chip including electrochemically generated receptor gradients to map threshold binding of uropathogenic bacteria under shear stress. The device is simple and bears the opportunity to study complex cell‐surface interactions.